Expressive Language Profiles in a Clinical Screening Sample of Mandarin-Speaking Preschool Children With Autism Spectrum Disorder. - Li Li; Yi (Esther) Su; Wenwen Hou; Muyu Zhou; Yixiang Xie; Xiaobing Zou; Ming Li (Journal of Speech, Language & Hearing Research, 2023)
urpose: This cross-sectional study aimed to depict expressive language profiles and clarify lexical–grammatical interrelationships in Mandarin-speaking preschoolers with autism spectrum disorder (ASD) during the administration of the simplified Chinese Psychoeducational Profile–Third Edition screening. Method: We collected naturalistic language samples from 81 (74 boys, seven girls) 2- to 7-year-old (M = 55.6 months, SD = 15.17) Mandarin-speaking children with ASD in clinician–child interactions. The child participants were divided into five age subgroups with 12-month intervals according to their chronological age. Computer-assisted part-of-speech tagging, constituency analysis, and dependency analysis addressed the developmental trajectories of early lexical and grammatical growth in each age subgroup. Results: Significant within-ASD differences were observed in content words, function words, and lexical categories. Nouns and verbs were the predominant lexical categories, while noun types overwhelmed verb types in children over 3 years old. The grammatical development of 5- to 6-year-old Mandarinspeaking children with ASD was better than that of 3- to 4-year-old children. The trends of syntactic structures, grammatical relations, and grammatical complexity in each age group were similar. Conclusions: Mandarin-speaking preschoolers with ASD produce more lexicons with increasing age. They preserve the noun bias as a universal mechanism in early lexical learning. Moreover, their developmental trajectories of grammatical growth were comparable in each age subgroup. In addition, their lexicons and grammar were synchronically developed during early language acquisition.